KEBERADAAN PEKERJA DISABILITAS DALAM PANDANGAN HAK ASASI MANUSIA - Zainal Abidin Pakpahan (Universitas Labuhanbatu, 2021)
Indonesia as a democratic country which has the freedom to enjoy its life legally must be protected, including disabilities, so that part of the constitutional right as regulated in Article 28 I paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Persons with disabilities are far from the government's attention in accommodating their rights so that people with disabilities are often marginalized by other groups so that they are less confident in expression by social interaction with other communities so that their existence is still far from a sense of security and protection legally even though they are rights human rights with disabilities must be treated equally and equally, which should be treated specifically because they have physical limitations, this means that the existence of persons with disabilities can have legal protection. prevailed. The problems in this regard, first, how is the existence of persons with disabilities in human rights, and legal protection in an effort to fulfill their rights. This study is a normative legal study aimed at finding and formulating legal arguments, through analysis of the subject matter. The technique of collecting legal materials is carried out by literature study. The approach used in this research is the statute approach, which is by examining the applicable legal rules relating to disabilities. This research concludes that the government seems still far from fulfilling the rights of persons with disabilities in human rights to obtain government understanding into multiple interpretations that can harm human rights with disabilities.Keywords: Existence, Disability, Human Rights